Social Justice in CALL-Mediated EFL Teaching: A Case of Indonesia: A case of Indonesia - Anas, Ismail; Basri, Muhammad; Nur, Sahril (Tamaddun Life, 2023)
Research into social justice in ELT has become increasingly critical. However, social justice in CALL, especially synchronous online EFL teaching, is scarcely investigated. Some lecturers are ignorant of the value of social justice in their Google Meet and Zoom classes. To fill this void, the study examined the lecturers’ perceived fairness, equity, respect, generosity, tolerance, and digital safety in SOLT. This article reports on a virtual case study that showcases the lecturers’ social justice and its transformation into their virtual learning environment. Twelve English lecturers agreed to participate in the study. Data were collected via a self-evaluation survey, virtual observation, and semi-structured interviews. As a result, the study shed light on four critical points: 1) the paucity of lecturers’ social justice knowledge and skills, 2) the call for negotiated pedagogy, 3) the absence of social justice in CALL pedagogy and 4) the need for social justice online community of practice. The study’s implication encourages language teachers to improve their social justice skills and literacies through CPD and CALL pedagogy.